An optical coherence tomography study of neointimal morphology and strut coverage at different time intervals from implantation of biodegradable polymer‐coated sirolimus‐eluting stents. Issue 2 (13th October 2017) - Legutko, Jacek; Gil, Robert J.; Buszman, Pawel E.; Kaluza, Grzegorz L.; Mintz, Gary S.; Roleder, Tomasz; Krol, Marek; Wojdyla, Roman; Pawlowski, Tomasz; Brzezinski, Michal; Kondys, Marek; Skwarna, Bartosz; et al.
Abstract: Objectives: The aim of the study was to capture the evolution of neointima after implantation of a biodegradable polymer–coated, sirolimus–eluting, cobalt–chromium coronary stent system (BP‐DES). Background: Optical coherence tomography (OCT) suggests that in‐stent neointimal morphology influences clinical outcomes after DES implantation. Methods: Sixty patients treated with single BP‐DES implantation were examined by quantitative coronary angiography (QCA) and OCT at 3, 6, and 12‐month follow‐up. Results: Median late lumen loss by QCA (mm) was 0.04 (IQR 0, 0.08), 0.17 (IQR 0, 0.32), and 0.14 (IQR 0.07, 0.31) at 3, 6, and 12‐month follow‐up respectively ( P = 0.03). OCT cross‐section multilevel analysis showed uncovered struts in 3.90%, 1.78%, and 0.02% of struts respectively ( P = 0.03). The corresponding malapposition rates were 0.12%, 0.04%, and 0%. Lipid‐rich neointima was observed only at 12‐month follow‐up in one restenotic lesion (0.77% cross‐sections) that was accountable for the only target vessel revascularization. The homogeneous pattern was prevalent at all three time points, but its incidence displayed an upward trend (3 months: 59%; 6 months: 71%; 12 months: 88%) despite no difference in neointimal volume between 6 and 12 months. Conversely, a trend could be observed of decreasing incidence of heterogeneous pattern as the follow‐up length increased. Conclusions: In this study of a single‐type BP‐DES, the majority of stent struts were covered within 3 months from implantation. While the quantitative neointimal accumulation plateaued at 6 months with no further significant increase beyond 6 months, the neointima continued to evolve qualitatively and mature along with better strut coverage between 6 and 12 months after implantation.